Implementation of digital academic administration system and its impact on the efficiency of educational services in D3 pharmacy study program - Hardian, Dafyar Eliadi; Marjoni, Mhd. Riza (Institute of Computer Science (IOCS), 2025)
Digital transformation in higher education demands the integration of an efficient academic administration system, especially in a vocational education environment such as the D3 Pharmacy Study Program which has high service complexity. This study was conducted to determine the extent to which the implementation of a digital academic administration system affects the efficiency of educational services. This study uses a quantitative approach with a descriptive correlational research type. Data were collected through distributing closed questionnaires to 92 respondents consisting of students, lecturers, and education staff. The instrument used adopted a five-point Likert scale with customized indicators on each variable. Data analysis was conducted using descriptive and inferential statistical techniques, including Pearson correlation test and simple linear regression. The results showed that there was a positive and significant relationship between the implementation of the digital academic administration system and the efficiency of educational services, with a correlation coefficient of 0.682 and R square of 0.465. This means that 46.5% of service efficiency can be explained by the effectiveness of the digital system implemented. The conclusion of this study shows that the digitalization of the academic administration system is able to improve the speed, accuracy, and affordability of educational services. For future development, it is recommended that the digital academic system be continuously updated by considering the specific needs of vocational education, as well as strengthening training and digital literacy for its users.